CONSUMER AGE INFLUENCE ON FOOD LABEL READING HABIT - Muhammad, Zeeshan, ZAFAR (Strategii Manageriale)
The objective of this paper was to detect the food label reading habit of consumer according to consumer age. To achieve this goal author of this paper has adopted five variables with independent and dependent status. Four variables were independent like reading complete food label, reading manufacturing date, reading expire date and reading ingredients. One variable was dependent like influence on purchase behavior. The data was collected through questionnaire and 350 questions were distributed among customers. Author has received 251 valid questions. The data was divided into two groups. The two groups were designed with respect to age range. In (Group I) the respondent’s age ranges was 20-25 and mean age was 23. Whereas in (Group II) the age was 26-30 and average age was 27. Correlation and regression test were conducted and results has unfolded the fact that there is a difference in both groups for food label reading habits. In Group I three variables significantly influence on purchase behavior of consumer while purchasing food items like reading manufacturing date, reading expire date and reading ingredients. In Group II only two variables like reading ingredients and reading manufacturing date has significant effect on purchase behavior of consumer while purchasing food products. Two variables were common in both groups like reading manufacturing date and reading ingredients. This result has also depicted that consumer normally, irrespective of age group; focus on manufacturing date, which give the freshness of food product, and ingredients to know the nutrients used in processing the food.